NUCLEAR GOVERNANCE IN THE ASIA-PACIFIC - Anthony, Mely Caballero; Trajano, Julius Cesar Imperial ([S.l.] : ROUTLEDGE, 2022)
The contributors to this book explore approaches to building a framework for nuclear governance in the Asia-Pacific - encompassing nuclear safety, security, and safeguards/non-proliferation. Nuclear governance collaboration offers an avenue for states in the Asia-Pacific to tackle the emerging opportunities for and challenges to the peaceful uses of nuclear energy and the civilian applications of nuclear and radioactive materials. The nature of national actions, bilateral initiatives and regional cooperation in capacity building taking place in East Asia provides a good foundation to pursue a more robust collaborative framework for nuclear governance in the wider Asia-Pacific region. The contributors to this book explore the most critical nuclear safety, security and non-proliferation issues faced by states in the Asia-Pacific and the growing cooperation spearheaded by Southeast Asian countries, China, Japan, South Korea and the United States. This book is a valuable read for academics working on security and strategic studies, international relations, non-traditional security issues as well as nuclear-related issues.
Keywords: Nuclear nonproliferation -- Asia; Nuclear energy -- Government policy -- Asia; POLITICAL SCIENCE / International Relations / Arms Control; POLITICAL SCIENCE / Political Freedom & Security / International Security